How Is Connectedness With Nature Linked to Life Satisfaction or Depression Among Chinese People Living in Rural Low-Income Households? A Serial Mediation Model - Yang, Chunyu; Chen, Xiaoyan; Yao, Jun; An, Jing (Frontiers in Public Health, 2022)
Objectives In this study a serial multiple mediation model is tested to investigate the potential sequentially-mediating effect of affect balance and social cohesion on the association between connectedness to nature and life satisfaction or depression. Methods A total of 675 Chinese people from Jiangsu province living in rural low-income households participated in the study. The Connectedness to Nature Scale (CNS), the Positive Affect and Negative Affect Scale (PANAS), the Social cohesion scale (SCS), the Satisfaction with Life Scale (SWLS), and the Patient Health Questionnaires (PHQ9) were measured in this paper. Results Results indicated that the multiple serial mediation of affect balance and social cohesion on the association between connectedness to nature and life satisfaction was significant among the full-size sample, the adult-report, and the old people report, but that this effect is relatively small. Specifically, serial mediation accounted for 2.01, 1.69, 2.67% of the total effect explained by connectedness to nature on life satisfaction, while it accounted for 2.66, 2.35, 2.91% of the total effect explained by connectedness to nature on depression among the full sample population, adults, and old people, respectively. Conclusions The findings corroborate the important roles of affect balance and social cohesion in activating connectedness to nature. We discussed the possible ways that affect balance and social cohesion might enhance life satisfaction and decrease depression for Chinese people living in rural low-income households. We also discussed the limitations of this study. More mechanisms could be considered in future studies.